The distribution of T‐cell subsets and the expression of immune checkpoint receptors and ligands in patients with newly diagnosed and relapsed acute myeloid leukemia. Issue 9 (30th November 2018) - Williams, Patrick; Basu, Sreyashi; Garcia‐Manero, Guillermo; Hourigan, Christopher S.; Oetjen, Karolyn A.; Cortes, Jorge E.; Ravandi, Farhad; Jabbour, Elias J.; Al‐Hamal, Zainab; Konopleva, Marina; Ning, Jing; Xiao, Lianchun; et al.
Abstract : Background: Phenotypic characterization of immune cells in the bone marrow (BM) of patients with acute myeloid leukemia (AML) is lacking. Methods: T‐cell infiltration was quantified on BM biopsies from 13 patients with AML, and flow cytometry was performed on BM aspirates (BMAs) from 107 patients with AML who received treatment at The University of Texas MD Anderson Cancer Center. The authors evaluated the expression of inhibitory receptors (programmed cell death protein 1 [PD1], cytotoxic T‐lymphocyte antigen 4 [CTLA4], lymphocyte‐activation gene 3 [LAG3], T‐cell immunoglobulin and mucin‐domain containing‐3 [TIM3]) and stimulatory receptors (glucocorticoid‐induced tumor necrosis factor receptor‐related protein [GITR], OX40, 41BB [a type 2 transmembrane glycoprotein receptor], inducible T‐cell costimulatory [ICOS]) on T‐cell subsets and the expression of their ligands (41BBL, B7‐1, B7‐2, ICOSL, PD‐L1, PD‐L2, and OX40L) on AML blasts. Expression of these markers was correlated with patient age, karyotype, baseline next‐generation sequencing for 28 myeloid‐associated genes (including P53), and DNA methylation proteins (DNA methyltransferase 3α, isocitrate dehydrogenase 1[IDH1], IDH2, Tet methylcytosine dioxygenase 2 [TET2], and Fms‐related tyrosine kinase 3 [FLT3]). Results: On histochemistry evaluation, the T‐cell population in BM appeared to be preserved in patients who had AML compared with healthy donors. The proportion of T‐regulatory cells (Tregs) in BMAs was higher in patients with AML than in healthy donors. PD1‐positive/OX40‐positive T cells were more frequent in AML BMAs, and a higher frequency of PD1‐positive/cluster of differentiation 8 (CD8)‐positive T cells coexpressed TIM3 or LAG3. PD1‐positive/CD8‐positive T cells were more frequent in BMAs from patients who had multiply relapsed AML than in BMAs from those who had first relapsed or newly diagnosed AML. Blasts in BMAs from patients who had TP53‐mutated AML were more frequently positive for PD‐L1. Conclusions: The preserved T‐cell population, the increased frequency of regulatory T cells, and the expression of targetable immune receptors in AML BMAs suggest a role for T‐cell–harnessing therapies in AML. Abstract : T‐cell subsets are preserved in the bone marrow of patients with acute myeloid leukemia. The expression of targetable immune checkpoints by T cells suggests that therapies harnessing T cells may benefit these patients.